2015
DOI: 10.1016/j.celrep.2015.08.035
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Orphan Receptor NR2F6 Is a Central Checkpoint for Cancer Immune Surveillance

Abstract: SummaryNuclear receptor subfamily 2, group F, member 6 (NR2F6) is an orphan member of the nuclear receptor superfamily. Here, we show that genetic ablation of Nr2f6 significantly improves survival in the murine transgenic TRAMP prostate cancer model. Furthermore, Nr2f6−/− mice spontaneously reject implanted tumors and develop host-protective immunological memory against tumor rechallenge. This is paralleled by increased frequencies of both CD4+ and CD8+ T cells and higher expression levels of interleukin 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 43 publications
4
79
1
Order By: Relevance
“…Based on previous studies and our present research, we believe that NR2F6 may also serve as a valuable druggable target. Recent studies indicate that NR2F6 serves as an immune checkpoint regulator that suppresses adaptive anticancer immune responses; this sets the stage for clinical validation of targeting NR2F6 for next‐generation immune‐oncological treatment regimens . Notably, Hermann‐Kleiter et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies and our present research, we believe that NR2F6 may also serve as a valuable druggable target. Recent studies indicate that NR2F6 serves as an immune checkpoint regulator that suppresses adaptive anticancer immune responses; this sets the stage for clinical validation of targeting NR2F6 for next‐generation immune‐oncological treatment regimens . Notably, Hermann‐Kleiter et al .…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that NR2F6 appears to be an intracellular immune checkpoint in effector T cells, directly repressing the NFAT/AP‐1 complex on both the interleukin 2 and interferon and cytokine promoters, attenuating their transcription. Moreover, adoptive transfer of Nr2f6‐deficient T cells into tumor‐bearing immune competent mice was shown to be sufficient to delay tumor outgrowth . Importantly, a previous study indicated that the ligand binding domain (LBD) on NR2F6 is highly evolutionarily conserved and appears to be essential for NR2F6 transcriptional activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they found that NR2F6 deletion has the same effect as blocking PD-1/PD-L1 interaction, considered an established immune checkpoint mechanism. They also found that NR2F6 directly represses the transcription of cytokine genes in T cells related to cancer cell rejection, such as interleukin (IL)-2, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ [39]. Therefore, NR2F6 may be a potential cancer therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews on NGFI-B-mediated pathways refer to references [7,[84][85][86]. [49]. It waits to demonstrate whether manipulation of the immune system via EAR2 would be a potential strategy for the immunotherapy of prostate cancer.…”
Section: Coup-tfsmentioning
confidence: 99%